IMPLEMENTASI KERJASAMA MERIDA INITIATIVE ANTARA AMERIKA SERIKAT DAN MEKSIKO DALAM PENANGGULANGAN PEREDARAN NARKOBA ILEGAL (2008-2010) - Pratiwi, Mega Wahyu (Global and Policy Journal of International Relations, 2018)
ABSTRACTMexico is a major supplier in drug trafficking in the United States. United States be used as market for Mexican cartels in the illegal drug trade. Drug trafficking that occurred in the border region between the two countries increasingly make the concerns of both countries as an increase in murder, violence, kidnapping. Crimes committed by Mexican drug cartels aiming to compete with other cartels and want to master the southwest border region. In addressing the problem of illegal drug trafficking in the border region, the two countries decided to create a cooperation agreement in the Merida Initiative. Cooperation Merida Initiative undertaken by the United States and Mexico in combating illegal drug trafficking is implemented through the Inter-institutional cooperation and the United States provide Military Aid to Mexico.Keyword: Merida Initiative, Inter-institusional Cooperation, Military Aid.DOI : https://doi.org/10.33005/jgp.v6i01.1882